Delayed effects of radiation exposure in a C57L/J mouse model of partial body irradiation with 2.5% bone marrow shielding - Beach, Tyler; Bakke, James; McDonald, J. Tyson; Riccio, Edward; Javitz, Harold S.; Nishita, Denise; Kapur, Shweta; Bunin, Deborah I.; Chang, Polly Y. (Frontiers in Public Health, 2024)
Introduction: Mouse models of radiation injury are critical to the development of medical countermeasures (MCMs) against radiation. Now that MCMs against hematopoietic acute radiation syndrome (H-ARS) have achieved regulatory approval, attention is shifting to develop MCMs against the adverse effects of gastrointestinal acute radiation syndrome (GI-ARS) and delayed effects of acute radiation exposure (DEARE). The C57L/J mouse model of partial body irradiation (PBI) with 2.5% bone marrow shielding (BM2.5) is being leveraged to examine both GI-ARS and DEARE effects. Within days of PBI, mice may develop H-and GI-ARS followed several months later by DEARE as a multi-organ injury, which typically involves the lung and kidney (L-and K-DEARE, respectively). The objective of this manuscript is to describe the dose response relationship and progression of radiation injury in the C57L/J mouse and to evaluate its suitability for use in DEARE MCM testing.In two separate studies conducted over two years, male and female C57L/J mice were exposed to PBI BM2.5 with one hindlimb shielded from radiation, representing approximately 2.5% bone marrow shielding/sparing. Mice were X-ray irradiated at doses ranging from 9 to 13 Gy at 10 to 12 weeks of age for the purposes of assessing ARS survival at 30 days and DEARE survival at 182 days post-irradiation. Clinical indicators of ARS and DEARE were determined by clinical observations, body weights, hematology, clinical chemistry, magnetic resonance imaging (MRI) of lung, and histopathology of selected tissues.Results: C57L/J mice developed canonical ARS responses of hematopoietic atrophy and gastrointestinal injury resulting in dose dependent mortality at doses ≥ 11 Gy between 1-and 15days post-irradiation. In animals that survived ARS, DEARE associated mortality occurred in dose dependent fashion at ≥ 9 Gy for both sexes between 60-and 159-days post-irradiation with histopathology examinations indicating lung injury as the primary cause of death in moribund animals.The PBI BM2.5 C57L/J mouse model reliably produced known H-and GI-ARS effects at doses greater than those resulting in DEARE effects. Because of this, the C57L/J mouse can be used to test MCMs against L-DEARE injury, while avoiding ARS associated mortality.